2019
DOI: 10.1111/clr.13425
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia compared to titanium dental implants in preclinical studies—A systematic review and meta‐analysis

Abstract: Objectives To evaluate whether zirconia implants demonstrate differences in hard and soft tissue integration compared to titanium implants in preclinical studies. Material and Methods In March 2017, electronic (MEDLINE, EMBASE) and hand search was performed to identify preclinical studies comparing zirconia and titanium implants. Primary outcomes were bone‐to‐implant contact (BIC) and removal torque out (RTQ), respectively, push‐in (PI) measurements. Secondary outcomes included biologic width (BW) dimensions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 106 publications
4
56
0
7
Order By: Relevance
“…As regards zirconia implants, the literature reports controversial, short-term and mainly anecdotal data [165,[170][171][172][173][174]. A recent systematic review with metaanalysis has evidenced similar potentialities of hard-and soft-tissue integration between zirconia and titanium implants, although with a slower initial osseointegration process detected in zirconia ones.…”
Section: Clinical Indication and Performancesmentioning
confidence: 99%
“…As regards zirconia implants, the literature reports controversial, short-term and mainly anecdotal data [165,[170][171][172][173][174]. A recent systematic review with metaanalysis has evidenced similar potentialities of hard-and soft-tissue integration between zirconia and titanium implants, although with a slower initial osseointegration process detected in zirconia ones.…”
Section: Clinical Indication and Performancesmentioning
confidence: 99%
“…Zirconia, tetragonal zirconia polycrystal (TZP) in particular, gained increasing importance due to their mechanical, esthetic and biocompatible performance for dental implants. In the recent reviews, it is reported that zirconia implants are a promising alternative to Ti with comparable osseointegration, a superior soft-tissue response in short-term outcomes [4][5][6][7] . However, more evidence data are needed to confirm the presently evaluated outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of zirconia as implant abutment material is rapidly increasing, since it is regarded as being more aesthetic and biologically friendly compared with traditional abutment material, titanium. 9 However, because it is bioinert and has low reactivity, the use of zirconia is challenging when it comes to fast integration with the surrounding tissue. 10 To address this issue, several surface modication approaches have been proposed to improve the biological performance of zirconia in terms of tissue responses: (i) modifying the surface topography by grinding, sand blasting, 11 or etching; 12 (ii) application of ultraviolet irradiation, 13 plasma spraying, 14 or laser treatment; 15 and (iii) coating of the surface with bioactive agents such as hydroxyapatite, 16 calcium phosphate, 17 chitosan, 18 type I collagen, 19 and bone morphogenetic protein 2.…”
Section: Introductionmentioning
confidence: 99%